THE CONCEPT AND FEATURES OF ADMINISTRATIVEAND LEGAL LIABILITY FOR VIOLATIONOF LEGISLATION IN THE FIELD OFINFORMATIZATION AND COMMUNICATIONS (Journal of Media studies, 2024)
The article examines the theoretical foundations of theapplication of administrative and legal responsibility for administrativeoffenses in the field of informatization and communication of modernsociety.Information technology has become a part of human life today. Ineveryday life, everyone in the world has such opportunities as prompt accessto information, communication and exchange of information, education,remote medical consultations and employment with the help of informationtechnology. However, at present, the development of information technologiesand communications, the fight against offenses in this area and ensuringcompliance with legislation remain relevant. The increase in administrativeoffenses in society, since informatization and communication have a directimpact on the life of a person and society, requires effective legal regulation ofmeasures of legal responsibility in this area. In the course of the work, a reviewof the works of domestic and foreign scientists was conducted, author'sdefinitions on “information law” were proposed, concepts on “the compositionof information offenses”, the most important concept in bringing to legalresponsibility, were developed. The purpose of the study is to analyze theconcept and specifics of administrative and legal responsibility foradministrative offenses in the field of informatization and communications andto identify problems that arise during the study.